Brentuximab vedotin as consolidation therapy after autologous stem-cell transplantation in patients with Hodgkin's lymphoma at risk of relapse or progression (AETHERA): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 9980 (9th May 2015) - Moskowitz, Craig H; Nademanee, Auayporn; Masszi, Tamas; Agura, Edward; Holowiecki, Jerzy; Abidi, Muneer H; Chen, Andy I; Stiff, Patrick; Gianni, Alessandro M; Carella, Angelo; Osmanov, Dzhelil; Bachanova, Veronika; et al.
Summary: Background: High-dose therapy followed by autologous stem-cell transplantation is standard of care for patients with relapsed or primary refractory Hodgkin's lymphoma. Roughly 50% of patients might be cured after autologous stem-cell transplantation; however, most patients with unfavourable risk factors progress after transplantation. We aimed to assess whether brentuximab vedotin improves progression-free survival when given as early consolidation after autologous stem-cell transplantation. Methods: We did this randomised, double-blind, placebo-controlled, phase 3 trial at 78 sites in North America and Europe. Patients with unfavourable-risk relapsed or primary refractory classic Hodgkin's lymphoma who had undergone autologous stem-cell transplantation were randomly assigned, by fixed-block randomisation with a computer-generated random number sequence, to receive 16 cycles of 1·8 mg/kg brentuximab vedotin or placebo intravenously every 3 weeks, starting 30–45 days after transplantation. Randomisation was stratified by best clinical response after completion of salvage chemotherapy (complete response vs partial response vs stable disease) and primary refractory Hodgkin's lymphoma versus relapsed disease less than 12 months after completion of frontline therapy versus relapse 12 months or more after treatment completion. Patients and study investigators were masked to treatment assignment. The primary endpoint was progression-free survival by independent review, defined as the time from randomisation to the first documentation of tumour progression or death. Analysis was by intention to treat. This trial is registered withClinicalTrials.gov, numberNCT01100502 . Findings: Between April 6, 2010, and Sept 21, 2012, we randomly assigned 329 patients to the brentuximab vedotin group (n=165) or the placebo group (n=164). Progression-free survival by independent review was significantly improved in patients in the brentuximab vedotin group compared with those in the placebo group (hazard ratio [HR] 0·57, 95% CI 0·40–0·81; p=0·0013). Median progression-free survival by independent review was 42·9 months (95% CI 30·4–42·9) for patients in the brentuximab vedotin group compared with 24·1 months (11·5–not estimable) for those in the placebo group. We recorded consistent benefit (HR <1) of brentuximab vedotin consolidation across subgroups. The most frequent adverse events in the brentuximab vedotin group were peripheral sensory neuropathy (94 [56%] of 167 patients vs 25 [16%] of 160 patients in the placebo group) and neutropenia (58 [35%] vs 19 [12%] patients). At time of analysis, 28 (17%) of 167 patients had died in the brentuximab vedotin group compared with 25 (16%) of 160 patients in the placebo group. Interpretation: Early consolidation with brentuximab vedotin after autologous stem-cell transplantation improved progression-free survival in patients with Hodgkin's lymphoma with risk factors for relapse or progression after transplantation. This treatment provides an important therapeutic option for patients undergoing autologous stem-cell transplantation. Funding: Seattle Genetics and Takeda Pharmaceuticals International.